2022
DOI: 10.31080/asvs.2022.04.0499
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Diurnal and Nocturnal Cub-Directed Social Interaction and Guarding Behaviour in Sumatran Tigers

Abstract: Felids are commonly housed in zoological collections worldwide. While aspects of their behaviour are well studied, there remain questions on best practice husbandry including during reproduction and breeding scenarios. In 2016, the Zoological Society of London's (ZSL) London Zoo held a pair of Sumatran tigers (Panthera tigris sumatrae) for the purpose of breeding. While they are believed to be solitary in the wild, many collections maintain their tigers in pairs, with some keeping pairs together during parturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
2
1
0
Order By: Relevance
“…The findings from this report suggest that social plasticity between groups may be more common within felids than has previously been acknowledged. Similar to the relationships found by Quintavalle Pastorino et al [ 45 ], the affiliation and tolerance observed between the father and his cubs offer a promising solution for alternative management strategies when housing felids in captivity.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The findings from this report suggest that social plasticity between groups may be more common within felids than has previously been acknowledged. Similar to the relationships found by Quintavalle Pastorino et al [ 45 ], the affiliation and tolerance observed between the father and his cubs offer a promising solution for alternative management strategies when housing felids in captivity.…”
Section: Discussionsupporting
confidence: 78%
“…Like most felids, tigers are known to spend a significant amount of the day inactive, with males typically more active than females [ 44 ]. While the findings of this study contradict such a notion, they mirror those found by Quintavalle Pastorino et al [ 45 ] which suggest the male was more inactive as a result of the female’s vigilance and care of the cubs. However, the male did spend considerably more of his time (12.7%) patrolling than the female which is typical of a male controlling his territory [ 46 ].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…By carefully managing breeding pairs and sharing individuals between institutions, zoos can maintain healthy populations of endangered reptiles and reduce the risk of inbreeding. This is accomplished by carefully planned breeding initiatives that prioritize preserving genetic variety and viability in zoo animal populations [21]. In order to maintain genetic variety, zoos establish controlled breeding programs for threatened or endangered species [21].…”
Section: )mentioning
confidence: 99%
“…This is accomplished by carefully planned breeding initiatives that prioritize preserving genetic variety and viability in zoo animal populations [21]. In order to maintain genetic variety, zoos establish controlled breeding programs for threatened or endangered species [21]. The danger of inbreeding can be decreased by using common population management techniques, such as keeping breeding couples or groups for repeated breeding and transfer plans, which enhance mate familiarity and breeding success [22].…”
Section: )mentioning
confidence: 99%